Impact of Instagram Reels vs. YouTube Shorts on Brand Engagement among Gen Z Changes (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Social media has transformed how brands communicate with consumers, with short-form video platforms emerging as key marketing channels. This study examines the impact of Instagram Reels and YouTube Shorts on brand engagement among Gen Z, focusing on brand discovery, engagement, and purchase intention, and comparing each platform’s effectiveness in building awareness.Prior research links short-form videos to brand visibility and purchase decisions, but most studies examine platforms in isolation, leaving gaps in direct comparison, platform-driven differences in student interaction, and links between platform preference and purchase intention among young Indian consumers.A descriptive design was adopted. Primary data were collected via a structured Google Forms questionnaire from 300 Gen Z respondents, mainly college students aged 17–26, using convenience sampling, supplemented by secondary data from journals and reports. Data were analysed using frequency, percentage, Chi-square, ANOVA, and Spearman correlation.Instagram Reels emerged as the most preferred platform (40%), while 35.7% used both equally. Most respondents (57.3%) watched brand-related short videos often, with 57.3% agreeing such videos aid brand discovery and 64% finding them more engaging. YouTube Shorts proved effective at retaining attention (59.7% watched until the end), and 58% credited algorithms for brand discovery. On purchase intention, 57% agreed short video ads influence product trials, and 52.7% reported higher purchase likelihood after viewing. All four hypotheses were supported, confirming significant links between brand discovery and engagement, engagement and purchase intention, platform preference and perceived engagement, and algorithms and trial decisions.Both platforms significantly shape brand engagement and purchase intention among Gen Z. Instagram Reels leads in preference and visual content, while YouTube Shorts shows stronger retention, with algorithms acting as a key bridge between content and consumer. Marketers should prioritise authentic, creative short-form content to engage young audiences. Future research could expand the sample, include other platforms, and examine brand loyalty.